Graphene: Visualization of Graphene on Various Substrates Based on Water Wetting Behavior (Adv. Mater. Interfaces 6/2016). Issue 6 (March 2016) - Xia, Kailun; Jian, Muqiang; Zhang, Wenlin; Zhang, Yingying
Abstract : In article number 1500674, K. L. Xia and Co‐workers demonstrate a water‐assisted approach for optical visualization of graphene. With condensation of water vapor, single crystal graphene domains on a variety of substrates become optically visible in seconds, which is arised from the unique wetting behavior of graphene. This approach is simple, green, nondestructive and repeatable, benefiting the characterization of graphene or other 2D materials.